Attachment dan homesickness siswa baru di lingkungan Pondok Pesantren - Salmi, Nailatul Fadhila; Yasmin, Maya (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
This research aims to describe the relationship between attachment and homesickness in new students at the Agam Regency Islamic boarding school. This study uses a quantitative approach. The population in this study were all new students at the Agam district Islamic boarding school, with a sample size of 322 people using a cluster sampling technique. Data collection used a scale with measuring instruments prepared by researchers based on the theories of Stroebe, Vliet, Hewstone, and Willis (2002) for the homesickness scale and Armsden & Greenberg (2009) for the attachment scale. Data analysis in research uses Pearson correlation techniques. The results of the analysis show that there is a relationship between attachment and homesickness, which statistically obtained a correlation coefficient of -0.424 and p = 0.01 (p<0.05). Keywords: homesickness, attachment, new students.